Principal component analysis of kicking kinematics in male and female soccer players - Navandar, A.; Kipp, K.; Navarro, E. (ISBS Proceedings Archive (Michigan), 2020)
This paper aimed to compare the angular motion in the sagittal plane of the hip and knee in male and female soccer players during the entire kicking cycle through principal component analysis (PCA). Kicking kinematics were recorded for 43 soccer players with a motion capture system. The kicking cycle was defined from toe off to the end of follow through and time-normalised hip and knee joint angles data were used as input to PCA. Four PC were extracted for hip and knee joint angles. Multivariate tests suggested an overall significant difference in the PC scores between females and males for hip flexion data (p = 0.001) but not for knee flexion data (p = 0.060). The results suggest that the primary difference in joint angle patterns between females and males occur at the hip joint. More specifically, females tend to exhibit smaller hip extension motion than their male counter-pair during the backswing phase (during the first 20% of the kicking cycle).